Being an effective English teacher through internship: Voices from the involved parties - Murtiningsih, Sri Rejeki; Swastika, Rafika Nedya; Puspitasari, Evi; Putri, Anisa Wahyu Dwi (Englisia: Journal of Language, Education, and Humanities, 2024)
The Indonesian national curriculum encourages higher education stakeholders to provide an internship program to increase students’ employability. In the field of education, an internship comes in the form of a teaching practicum where all interns or prospective teachers get hands-on experience in schools to develop the characteristics of effective teachers. To identify areas for improvement in the running program, gathering insights from those involved is necessary. The current case study details how the internship program facilitates effective teaching for prospective teachers. This research also discussed recommendations from involved parties to obtain reliable references to improve the program. The data were collected by interviewing four prospective teachers, two university supervisors, and two mentor teachers. This study used transcribing, member checking, and coding to analyze the interview results. The data revealed that the four steps in the program, i.e., deployment, observation, coaching, and teaching practices, helped the prospective teachers to build a robust construct of effective teachers, including socio-affective skills, pedagogical competence, content knowledge, and personal qualities. Additionally, the findings demonstrated the participants’ suggestions related to several technical issues of the program and recommendations to the prospective teachers regarding what they should do in joining the program. Regardless rooms of improvements that the program should follow-up, all participants agree to say that the practice teaching facilitates prospective English teachers to develop competencies of being an effective teacher.